KOMPONEN SEL JARINGAN IKAT - Wangko, Sunny; Karundeng, Ronny (JURNAL BIOMEDIK : JBM, 2014)
Abstract: Connective tissue is distributed in all parts of the body and its main function is to connect cells and tissues. Most of the embryonic connective tissues are derived from embryonal messenchymal tissues. There are a variety of connective tissues which are compatible with their functions and locations. The general difference of all connective tissues is the arrangement and composition of intercellular matrix. Connective tissues are composed of two major components: cells and intercellular matrices. Connective tissue cells, fixed cells or wandering cells, have their special functions which support each other to maintain the optimal histophysiology of the connective tissue.Keywords: connective tissues, cells, histophysiologyAbstrak: Jaringan ikat tersebar luas di seluruh bagian tubuh dengan fungsi utama untuk menghubungkan berbagai komponen sel atau jaringan. Hampir seluruh jaringan ikat embriologik berasal dari jaringan mesensimal embrional. Terdapat berbagai jenis jaringan ikat yang sesuai dengan fungsi dan lokasinya. Perbedaan utama dari berjenis-jenis jaringan ikat tersebut berdasarkan susunan dan komposisi matriks intersel. Jaringan ikat terdiri dari dua komponen dasar utama yaitu sel dan matriks intersel. Sel-sel jaringan ikat baik yang tetap maupun yang bebas mempunyai fungsi khusus masing-masing yang saling melengkapi untuk mempertahankan keutuhan histofisiologi jaringan ikat.Kata kunci: jaringan ikat, sel, histofisiologi